Implementation of ICT using Hawgent dynamic mathematics software to teach probability. Issue 1 (May 2021) - Wijaya, T T; Zhou, Y; Purnama, A; Yunita, W; Mukhlis,; Salamah, U
Abstract: Technology is one of the media to enhance the quality of teaching. Technology can cause the teaching-leaming process to be more interactive and less tedious. According to Indonesia's national examination result, the probability topic still got a low score in the past three years. This data is supported with the observation on junior high school students that students' mathematics ability towards the basic concept of Probability is still low. This research aims to make education in education to guide Senior High School students to understand Probability. This study uses a mix of research development using the ADDIE model and quasi-experiment to analyze the class that uses technology Hawgent with the class that uses the conventional teaching method. According to this observation, researchers designed technology-based learning using Hawgent to support a Senior High School student to grasp the basic concept of Probability better and improve students' learning outcomes. According to the validation and discussion, the Hawgent's development as learning media has been validated by the media and material experts that falls in the excellent category or is applicable. The test result on the students also falls in the satisfying category.